Analyzing Medicine by Means of Reprint Requests - Onuigbo, W. I. B. (Methods of Information in Medicine, 1985)
Authors are commonly asked for reprints of their publications. There is need to promote awareness of the usefulness of such requests in gathering medical information. By way of illustration, this study focusses on how requests from the United States of America enabled an African author to collect interesting data on that country’s military medicine with reference to such parameters as the specialties of the requesters, the selective nature of their requests, and even women’s inferior position in science. It is concluded that the reprint request is a neglected tool which has research potentialities in medical informatics.
Keywords: Military Medicine; Reprint Requests; Informatics